Global Attractor for Second-Order Nonlinear Evolution Differential Inclusions. (4th March 2021) - Su, Guangwang; Lin, Funing
Abstract : In this paper, we address the model of global attractor formulated in the form of evolution differential inclusions with second order in Banach spaces. Firstly, based on the fixed point theorem, the existence result of mild solutions is deduced. Then, by implementing the measure of noncompactness, the existence of global attractor associated with m -semiflow is validated. Finally, a concrete application of the main result is demonstrated to enhance the practical signification.